A secure and decentralised SIP for mobile ad hoc networks. (2018) - Hussain, Mohammed; Khedher, Dhafer Ben
Mobile ad hoc networks (MANETs) are infrastructureless and can be set up temporarily. They can host a wide range of conferencing applications, such as audio/video conferencing. Decentralised versions of session initiation protocol (SIP) fit the lightweight and scalability requirements needed for MANETs. Security in decentralised SIP has not yet been addressed. This paper presents an authentication scheme for decentralised SIP. The scheme allows the members of a decentralised SIP-based conference to securely perform SIP operations. The scheme employs identity-based signatures cryptography. The practicality and effectiveness of the scheme is illustrated using a working prototype.